The Return of the Undead: Vegetable vampires, Fantastic plants, Botanical monstrifications in “La orquídea” by León Fernández Guardia and “Orquídea” by Andrés F. Wassington - Huertas Arredondo, Kimberly (2025)
In this article we analyze the vegetable vampirism in "La orquídea" (1907) by the Costa Rican writer León Fernández Guardia and "Orquídea" (2006) by the Argentinean Andrés Federico Wassington,through theoretical-methodological tools from comparative literature (tematology), botany, plant-horror and Ecogothic. This critical perspective allows us to argue that these stories are, perhaps, the first texts of the vegetal fantastic in Latin American literature, interested in reproducing, explicitly and during the twentieth and twenty-first century, the figure of the vampire, from the orchidological flora. The selected textualities bring a renewal of the specificity of the discourse of the fantastic, while offering a new look through the insertion of new codes that revive and resignify the modern monstrous plant and, in passing, the vampire monster manifested in the European gothic-fantastic vampire tradition, precisely with the tropicalization of the feeling or effect of the fantastic (i.e., the monstrosity of the character, the grotesque and the abject body) and the incorporation of vegetable vampires.